Improving Mathematics Learning Outcomes through Contextual-Based Learning Video Media for Fourth Grade Elementary School Students - Ni Made Aprelia Merti Dewi; Dewi Anzelina; Ikrima Maulida (Jurnal Media dan Teknologi Pendidikan, 2025)
This study was motivated by the low mathematics learning outcomes of elementary school students, which are attributed to the lack of connection between instructional materials and real-life contexts as well as the limited variation in teaching methods. The purpose of this research is to analyze the effectiveness of using contextual-based instructional video media in improving the mathematics learning outcomes of fourth-grade students. This study employed a research and development design using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects consisted of 32 students who participated as trial respondents. The research data included qualitative and quantitative data, collected through questionnaires, interviews, and written tests. Data were analyzed using descriptive qualitative and quantitative methods to assess the validity, practicality, and effectiveness of the media. The results indicate that the contextual-based video learning media was effective in enhancing conceptual understanding and learning outcomes, as evidenced by the increased engagement, enthusiasm, and ability of students to connect mathematical concepts with daily experiences. The findings suggest that implementing contextual-based media can foster meaningful and interactive learning. The implications emphasize the importance of developing culturally and contextually relevant digital learning media and enhancing teachers’ competencies in integrating educational technologies creatively and effectively.